Production optimization model to increase order fulfillment by applying tools under the Lean Green philosophy and TPM in plastic manufacturing SMEs - Garrido-Silva, Ricardo (2022)
The plastic sector sustains an important growth based on production worldwide and nationally during the last years. However, this growth in production can be affected by the various problems that the sector sustains, harming the availability of plastic products and thereby affecting customers, this impact is reflected in customer losses due to the non-fulfillment of orders or additional payments for penalties imposed by them. In this context, companies in the plastic sector aim to reduce machine downtime rates to increase availability and thereby maintain smooth production and thus increase the order fulfillment rate. After the above, in the research, the problem that generates a low rate of order fulfillment is due to the constant blowing machine shutdowns in the plant. Therefore, it is proposed to design a model based on the Lean Manufacturing philosophy, using tools such as 5S, SW, TPM and SMED, based on applications of the Lean Green philosophy; with the aim of reducing stops in the blowing machine making it more efficient and environmentally friendly. This research emphasizes the most representative product of the company, the drums, developing the diagnosis in the blowing process, which, the root causes were quantified with respect to the main problem, through the tools of the Lean Manufacturing philosophy it is proposed to address each cause and mitigate them. Finally, the model that has been proposed manages to reduce the rate of machine shutdowns by 55.48%, giving greater availability to the blowing machine and with it a better production flow, which generates an increase in the order fulfillment rate by 74.59%. In this way, a precedent is achieved in the plastic sector regarding the improvement of blowing processes.